Pulmonary oxygen uptake and muscle deoxygenation responses during ramp incremental exercise and moderate- and heavy-intensity exercise subsequent to priming exercise in type 2 diabetes. - GILDEA, NORITA (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2017)
Middle-aged and young individuals with uncomplicated type 2 diabetes mellitus (T2DM) consistently demonstrate impairments in submaximal and maximal exercise performance, which are independent of obesity, and present in the absence of clinically apparent cardiovascular disease. Such limitations have the potential to contribute to the tenacious excess cardiovascular and all-cause mortality observed in T2DM. Whilst the precise pathophysiological mechanisms responsible for this exercise intolerance remain to be elucidated, with both central and peripheral factors likely implicated, the primary aim of this thesis was to further investigate those mechanisms with an emphasis on the contribution of peripheral factors. As such, cardiorespiratory and estimated microvascular responses were simultaneously investigated during graded ramp incremental cycle exercise and during submaximal cycling exercise at moderate- and heavy-intensities subsequent to a prior heavy-intensity “priming” exercise. Given that muscle oxygen supply may limit maximal exercise capacity in T2DM, Experiment 1, examined the influence of T2DM on the profile of muscle fractional oxygen (O2) extraction (estimated using deoxygenated haemoglobin and myoglobin [HHb+Mb]) during ramp incremental cycle exercise in 17 middle-aged individuals with T2DM (48 ± 7 yr; 31.9 ± 4.8 kg.m-2; 12 males/5 females) and 17 individuals without T2DM (ND/controls) (44 ± 8 yr; 30.8 ± 3.5 kg.m-2; 12 males/5 females). Maximum oxygen uptake (VO2max) was significantly reduced in individuals with T2DM compared with controls (22.5 ± 3.7 vs. 28.6 ± 5.5 mL.kg.min-1), representing a reduction of 21% in peak exercise capacity. This impairment was accompanied by the demonstration of a steeper primary slope of the bi-linear regression of relative [HHb+Mb] (% [HHb+Mb]) as a function of relative power output (%PO) in individuals with T2DM (1.48 ± 0.46 vs. 1.14 ± 0.21), thus, indicative of a greater rate of fractional O2 extraction for a given increase in oxygen uptake (VO2). This suggests a reduced O2 delivery is a likely underlying cause of exercise intolerance during a maximum graded test in T2DM. The subsequent three experiments were designed to investigate the influence of heavy-intensity (50% delta) priming exercise on the VO2 and [HHb+Mb] kinetics responses during subsequent moderate-, heavy- and heavy-intensity work-to-work (initiated from an elevated baseline) exercise bouts in T2DM. Experiment 2 examined the influence of priming exercise and T2DM on the VO2 and [HHb+Mb] dynamic response during moderate-intensity (80% ventilatory threshold (VT)) cycle exercise. Twelve middle-aged individuals with T2DM (48 ± 8 yr; 32.1 ± 5.6 kg.m-2; 7 males/5 females) and 12 controls (44 ± 9 yr; 30.4 ± 4.1 kg.m-2; 7 males/5 females) were tested. Individuals with T2DM demonstrated an accelerated rate of adjustment of the primary phase of the VO2 kinetics (τV̇ O2p) response (43 ±41 vs. 34 ± 11 s), whilst Δ[HHb+Mb]kinetics remained unchanged (29 ± 6 vs.28 ± 6, s) in a subsequent bout of primed moderate-intensity (80%VT) cycling exercise. This was accompanied by the amelioration of an ‘overshoot’ relative to steady-state in the Δ[HHb+Mb]/ΔV̇ O2 ratio (1.18 ± 0.17 vs. 1.05 ± 0.15) in the primed on-transient exercise response, attributed to an enhanced matching of microvascular O2 delivery to utilisation consequent to priming exercise. Experiment 3 examined the influence of priming exercise on VO2 and Δ[HHb+Mb] kinetics during heavy-intensity cycle exercise in T2DM. Twelve middle-aged individuals with T2DM (46 ± 8 yr; 31.4 ± 4.8 kg.m-2; 8 males/4 females) and 12 controls (43 ± 10 yr; 30.6 ± 3.8 kg.m-2; 8 males/4 females) were tested. Priming exercise significantly accelerated the overall VO2 kinetics profile or mean response time (MRT) in the subsequently primed heavy-intensity exercise bout (75 ± 10 vs. 55 ± 14 s). This was facilitated via a significant acceleration of τV̇ O2p (37 ± 10 vs. 31 ± 9 s) combined with a substantial reduction (P=0.1) in the VO2 amplitude of the slow component (0.26 ± 0.15 vs. 0.15 ± 0.07 L.min-1). Given that this acceleration of the overall VO2 kinetics occurred in the presence of an unaffected dynamic Δ[HHb+Mb]response (33 ± 27 vs. 16 ± 6) is thus further supportive of a superior O2 delivery relative to utilisation associated with heavy-intensity priming exercise. Healthy individuals display a constrained VO2 kinetics response when constant-load exercise is initiated from an elevated baseline (work-to-work). Thus, when combined with the notion of an already constrained muscle O2 supply in T2DM, the inclusion of a priming exercise intervention with the work-to-work model should provide superior insight into potential mechanisms implicated in the impaired VO2 kinetics response consistently demonstrated in T2DM. Thus, in Experiment 4 the influence of priming exercise on pulmonary oxygen uptake and muscle deoxygenation kinetics during heavy-intensity, work-to-work (w-to-w) cycle exercise in T2DM was investigated. Seven middle-aged individuals with T2DM (46 ± 8 yr; 30 ± 6 kg.m2; 3 males/4 females) and 7 controls (41 ± 10 yr; 31 ± 5.0 kg.m-2; 3 males/4 females) were tested. The MRT of the VO2 kinetics during w-to-w cycling transitions was significantly accelerated subsequent to the prior bout of heavy-intensity priming exercise (72 ± 10 vs. 53 ± 19 s). This was a consequence of a significant reduction (~40%) in the amplitude of the VO2 slow component (0.13 ± 0.15 vs. 0.08 ± 0.10 L.min-1), a substantial reduction of ~22% in primary phase of the VO2 kinetics response (54 ± 14 vs. 42 ± 17 s), with a tendency for the overall dynamic responses of Δ[HHb+Mb] (MRT) to be accelerated (52 ± 32 vs. 37 ± 24 s; P<0.10). Thus, the speeding of the VO2 MRT following priming exercise was attributed to a combination of an increased O2 delivery and the potential enhancement of motor unit recruitment. Thus, the accumulated data in this thesis offer a further insight into potential contributory mechanisms for the evidenced exercise intolerance in individuals with T2DM. The demonstration of a greater reliance on O2 extraction for a given increase in power output (PO) suggests that a reduced O2 delivery is in fact an important fundamental cause of exercise intolerance during maximal graded efforts in T2DM. This is further corroborated by the demonstration of improvements in oxidative metabolism with a concomitant improvement in the matching of O2 delivery to utilisation at a microcirculatory level consequent to an acute bout of heavy-intensity priming exercise, prior to both moderate- and heavy-intensity exercise (with and without an elevated baseline). Collectively, these findings suggest that factors beyond the heart substantially contribute to the diminished exercise tolerance consistently evidenced in T2DM
APPROVED
Keywords: Type 2 diabetes, priming exercise, VO2 kinetics, muscle deoxygenation